2012
DOI: 10.1093/cid/cis612
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing HIV Transmission Networks Across the United States

Abstract: Background. Clinically, human immunodeficiency virus type 1 (HIV-1) pol sequences are used to evaluate for drug resistance. These data can also be used to evaluate transmission networks and help describe factors associated with transmission risk.Methods. HIV-1 pol sequences from participants at 5 sites in the CFAR Network of Integrated Clinical Systems (CNICS) cohort from 2000-2009 were analyzed for genetic relatedness. Only the first available sequence per participant was included. Inferred transmission netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
109
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 37 publications
13
109
4
Order By: Relevance
“…[1][2][3][4][5][6] The identification of transmission clusters can support epidemiologically linked transmission events, 7 identify putative transmission chains, 8 and reveal mixing between key risk groups and geographic subpopulations. 9 Transmission clusters of HIV infections are typically defined using either genetic distances among sequences 4 or genetic distances in addition to branch support values (e.g., bootstrap values). 3 However, genetic distance and branch support cutoffs markedly vary between studies and the rationale for a given cluster definition is rarely specified.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The identification of transmission clusters can support epidemiologically linked transmission events, 7 identify putative transmission chains, 8 and reveal mixing between key risk groups and geographic subpopulations. 9 Transmission clusters of HIV infections are typically defined using either genetic distances among sequences 4 or genetic distances in addition to branch support values (e.g., bootstrap values). 3 However, genetic distance and branch support cutoffs markedly vary between studies and the rationale for a given cluster definition is rarely specified.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular epidemiology of HIV-1 has been studied extensively both globally, (Faria et al, 2014;Wertheim et al, 2014) and in limited geographic settings, (Aldous et al, 2012;Bruhn et al, 2014;Ciccozzi et al, 2013;Esbjornsson et al, 2016;Kouyos et al, 2010;Mendoza et al, 2014;Paraskevis et al, 2015) to increase the understanding of the drivers of HIV-1 transmission and to increase the focus of preventive strategies (Brenner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Transmission networks inferred from genetic sequences allow the study of viral dynamics on a local or national level. [14][15][16][17][18][19] Moreover, these networks provide the means to improve the effect of targeted treatment intervention. 20 Recent work by Wertheim et al 2 has demonstrated how the global diversity of HIV can be efficiently queried for transmission links by comparing genetic distances between isolates.…”
mentioning
confidence: 99%